A review of alternative strategies for improving farmer-managed irrigation systems in Sri Lanka - Dayaratne, M.H.S. (International Irrigation Management Institute, 1991)
The present study is an outcome of research carried out by the author under the Farmer-Managed Irrigation Systems (FMIS) Program of IIMI. The study was based mostly on available literature, and partly on the author's experience in the small-scale irrigation sector under the District Integrated Rural Development Programs (Hambantota and Badulla) of the Ministry of Plan Implementation and under the FMIS theme of IIMI in the North Central Province. The study reviewed three government strategies and two nongovernment strategies which have been implemented as assistance programs to improve and enhance the small irrigation sector during the last two decades. It was also based largely on the research findings and presentations made at workshops on specific subjects conducted by IIMI and the Agricultural Research and Training Institute (ARTI).